O impacto das agências reguladoras de saúde no desempenho dos hospitais privados no Brasil - Silva, Gisele da (2017)
The study advances the understanding of the effects of health sector regulation on the performance of private hospitals in Brazil. Health regulatory agencies, ANS and ANVISA, are part of the Public Administration structure, possess a high degree of technical specialization and establish control actions to stimulate the production of public goods and services that guarantee the interests of the population. The search of hospital managers for appropriate management models and tools for evaluating hospital performance, compatible with the complexity of the supplementary health system to which they are inserted, is vital for the maintenance of services. Within this context, this research aims to identify the impact of health regulatory agencies on the performance of private hospitals in Brazil. The theoretical lens of intentional theory (NORTH, 1990) was used to better understand the mechanisms of institutionalization. To this end, a mixed-method study was conducted to: identify and classify hospital performance indicators through bibliographic research; determination and categorization of regulatory actions of ANS and ANVISA through documentary research; and the estimation of the impact generated in the hospital performance by the regulatory actions, through a survey with the hospital managers. The results suggest that regulatory actions generate a positive impact on the overall performance of the hospital, according to the perception of 91.3% of managers about ANVISA and 61.9% about ANS. In addition, the findings suggest that the factors "definitions of technical requirements for the operation of services" and "monitoring mechanisms" of ANVISA, have a negative impact on economic and financial performance. As well as, the establishment of the "roll of procedures for coverage" of Health Care Providers, negatively impact the three areas of hospital performance explored: financial, operational and care. Finally, the statistical tests carried out in the search for differences in the managers' responses in relation to the position they occupy and the size of the hospital where they work did not present significant statistical relationships and little explanatory power.